KONSTRUKSI IDENTITAS PEREMPUAN JAWA DALAM NOVEL WIGATI: ANALISIS STILISTIKA LEECH DAN SHORT - Imron Habib; Sariban; Irmayani (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
This study is motivated by the importance of reading Khilma Anis’s novel Wigati: Lintang Manik Woro as a work of pesantren literature that brings together religiosity, Javanese culture, the world of keris, and Javanese women’s identity. In this context, Javanese women are often positioned within the tension between the values of politeness, obedience, religiosity, and the capacity to negotiate tradition. This study aims to explain the construction of Javanese women’s identity in Wigati: Lintang Manik Woro through Leech and Short’s stylistic approach. The main problem of this research stems from the tension between the normative image of Javanese women, which is often associated with politeness, obedience, and an attitude of nriman, and the representation of female characters in the novel who appear active in tracing their origins, interpreting inheritance, and negotiating the authority of pesantren and Javanese culture. This study employs a descriptive qualitative method, with data collected through library research, close reading, note-taking, and data coding. The primary data source is the ninth edition of the novel Wigati: Lintang Manik Woro, published in 2019. The research data consist of words, phrases, sentences, dialogues, and narratives that contain lexical, grammatical, figurative language, cohesion, and contextual categories as proposed by Leech and Short. The data analysis is supported by Stuart Hall’s theory of representation to interpret identity as a textual construction shaped through language. The results of the study show that pesantren religious diction, Javanese cultural vocabulary, keris-related terminology, short sentences, repetition, interrogative forms, keris metaphors, and the context of pesantren and Javanese culture function as means of representing Javanese women’s identity. This identity is constructed as that of a female santri who is religious and knowledgeable, a cultural inheritor, an nriman yet non-passive individual, a wounded inner subject, and a woman capable of negotiating patriarchal norms. Thus, language in the novel does not merely function as an aesthetic element but also becomes a space for producing Javanese women’s identity that is layered, negotiated, and continuously shaped through linguistic practices.